GAYA HIDUP RUMAH TANGGA DALAM MENGONSUMSI BUAH-BUAHAN DI BANDAR LAMPUNG - Tunjung Andarwangi; Yaktiworo Indriani; Fembriarti Erry Prasmatiwi (Lampung University, 2016)
This research aims to determine the fruit consumption lifestyle and eating pattern of fruits, and the affecting factors on the demand of fruits in the household having primary school age children in Bandar lampung. This research samples are 60 households that have primary school age children. The data is collected in November 2014-April 2015 and analyzed descriptively and statistically by seemingly unrelated regression (SUR). The results of this research showed as follows. The household lifestyle in consuming fruits in side of activity was indicated that 75.0% of the households bought fruits routinely, but 66.7% were rarely consuming fruits in various serving and 73.3% preferred local than import fruits. As much as 98.3% households had opinions that fruits contains a lot of vitamins, minerals and fibers. Banana, papaya, watermelon, snakeskin fruit and avocado were the most consumed fruits in the households in which monthly average consumption was 2-8 times with each weight were 3.8 kg, 2.5 kg, 1.9 kg, 0.9 kg, 0.8 kg. The demand of banana was influenced by the price of banana and total income; of papaya was influenced by the price of papaya, banana and avocado; of watermelon was influenced by the price of watermelon and avocado; of snakeskin fruit was influenced by the price of watermelon and sugar; and of avocado was influenced by the price of avocado. Key words: demand, eating pattern, fruits, lifestyle